2020
DOI: 10.1093/nar/gkz1231
|View full text |Cite
|
Sign up to set email alerts
|

A key interaction with RPA orients XPA in NER complexes

Abstract: The XPA protein functions together with the single-stranded DNA (ssDNA) binding protein RPA as the central scaffold to ensure proper positioning of repair factors in multi-protein nucleotide excision repair (NER) machinery. We previously determined the structure of a short motif in the disordered XPA N-terminus bound to the RPA32C domain. However, a second contact between the XPA DNA-binding domain (XPA DBD) and the RPA70AB tandem ssDNA-binding domains, which is likely to influence the orientation of XPA and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 63 publications
6
70
0
Order By: Relevance
“…RPA physically interacts with over three dozen DNA processing enzymes and recruits several of them onto DNA ( 4 ). Finally, RPA hands-off the DNA to these enzymes and correctly positions them to facilitate their respective catalytic activity ( 5 ). Plasticity for such multiplexed functional roles for RPA can be ascribed to its flexible structure and its corresponding context-dependent interactions with DNA ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…RPA physically interacts with over three dozen DNA processing enzymes and recruits several of them onto DNA ( 4 ). Finally, RPA hands-off the DNA to these enzymes and correctly positions them to facilitate their respective catalytic activity ( 5 ). Plasticity for such multiplexed functional roles for RPA can be ascribed to its flexible structure and its corresponding context-dependent interactions with DNA ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such movement may represent a transition state on the path to a stable “unwound” state. In our samples, however, such transition may have been present only transiently, easily reverting back to the “pre-unwound” state; complete and stable conversion into the “unwound” state may require additional factors such as Rad14(XPA) and RPA 83 85 accompanied by the large movement of Rad3/XPD as described above 43 . Also, a longer DNA segment on the 5' side of the lesion than our current design may be required in order to permit a larger bubble formation.…”
Section: Discussionmentioning
confidence: 86%
“…In previous studies we often observed that the interaction of RPA with partner proteins have, in addition to a readily characterized interaction with RPA70N or RPA32C, a secondary interaction with the tandem high affinity DNA binding domains RPA70AB (e.g. (27)). These interactions are invariably weaker than the contacts with the corresponding protein recruitment domain.…”
Section: Resultsmentioning
confidence: 99%